A novel characterization method of fiber reinforced polymers with clustered microstructures for time dependent mass transfer - Jain, D.; Mukherjee, Abhijit; Bera, T. (2017)
© 2017 Walter de Gruyter GmbH, Berlin/Boston. Some variation in the topological distribution of fibers inside the matrix phase of fiber reinforced polymers (FRP) is inevitable. Such irregularities can accelerate moisture diffusion and adversely affect the life of FRP. This paper presents a hierarchical technique for characterization of clustered microstructures and their transient moisture diffusion response. The clustering descriptors are derived for different fiber volume fractions (dilute to dense) for the quantitative definition of a given fiber matrix architecture. The metrics are normalized to remove dependence on volume fraction. The microstructures are analyzed for Fickian moisture diffusion. Suggested descriptors show a good correlation with transient diffusion response in relation to saturation time. The results can be used to predict the time-dependent moisture diffusion response of FRPs for any given fiber volume fraction.